Financial Derivatives and the Globalization of Risk - LiPuma, Edward, 1951-; Lee, Benjamin, 1948- (Book collections on Project MUSE., 2004)
Cultural studies exploration of the implications of the circulation of increasingly abstract forms of capital in the contemporary global economy.